The impact of patient characteristics and disease-specific factors on first-line treatment decisions for BRAF-mutated melanoma: results from a European expert panel study. Issue 4 (August 2018) - Ascierto, Paolo A.; Bastholt, Lars; Ferrucci, Pier F.; Hansson, Johan; Márquez Rodas, Iván; Payne, Miranda; Robert, Caroline; Thomas, Luc; Utikal, Jochen S.; Wolter, Pascal; Kudlac, Amber; Tuson, Harriet; et al.
Abstract : Treatment decisions for advanced melanoma are increasingly complex and guidelines provide limited advice on how to choose between immunotherapy and targeted therapy for first-line treatment. A Delphi study was carried out to understand which patient characteristics and disease-related factors inform clinicians' choices of first-line treatment for BRAF-mutated melanoma. Twelve European melanoma specialists experienced in using immunotherapies and targeted agents participated in a double-blind two-phase Delphi study. In phase 1, participants completed a questionnaire developed after reviewing patient characteristics and disease-related factors reported in trials, clinical guidelines, and health technology assessments. Phase 2 was an expert panel meeting to explore outstanding issues from phase 1 and seek consensus, defined as 80% agreement. Twenty patient-related and disease-related characteristics were considered. There was consensus that tumor burden (83% of clinicians) and disease tempo (83%) are very or extremely important factors when selecting first-line treatment. Several components were deemed important when assessing tumor burden: brain metastases (82% of clinicians) and location of metastases (89%). There was consensus that disease tempo can be quantified in clinical practice, but not on a formal classification applicable to all patients. Lactate dehydrogenase level is a component of both tumor burden and disease tempo; all clinicians considered lactate dehydrogenase important when choosing first-line treatment. The majority (92%) did not routinely test programmed death ligand-1 status in patients with melanoma. Clinicians agreed that choosing a first-line treatment for advanced melanoma is a complex, multifactorial process and that clinical judgment remains the most important element of decision-making until research can provide clinicians with better scientific parameters and tools for first-line decision-making. Abstract : Supplemental Digital Content is available in the text.